Buah Buton at the House of Dato’ Muar Bongkok: The Context of Nature as an Interpretation of the Character of Adat Perpatih Customary Leaders - Fakhrur Razi Maamor,; Sabzali Musa Kahn,; Basitah Taif,; Mohd Rosli Saludin, (Advances in Humanities and Contemporary Studies, 2023)
In this world, there are many methods to emphasize a person's essence and character, including the buah buton, which is a sign of identification. The goal of this article is to explain the relationship between the natural environment, personality and values found at Dato’ Muar Bongkok's house in Luak Tanah Mengandung, Negeri Sembilan. The study also includes two ways for gathering data, one of which is fieldwork by inspecting the traditional houses involved. Meanwhile, the interview included descendants, local communities, and experts in Adat Perpatih. According to the field study, the buah buton hangs in the section that represents the traditional leader. The symbolism relates to the leader's character, who alludes to nature as a setting in the development of traditional art. As a result, this article proposes that the buah buton may be employed as a visual communication sign that links understanding in a positive manner. For example, it is used as a gathering location for leaders who advocate for the beliefs and rights of the people in the nation.